Division of labor in stable social hierarchy of the independent-founding wasp Mischocyttarus (Monocyttarus) cassununga, von Ihering (Hymenoptera, Vespidae) - Murakami, A. S N [UNESP]; Desuó, I. C. [UNESP]; Shima, S. N. [UNESP] (Universidade Estadual de Feira de Santana, 2013)
In colonies of independent-founding wasps, social organization is characterized by a division of labor wherein the most dominant female (the queen) spends more time on the nest comb during its development, while the subordinates (workers) perform most of the foraging. The present study aimed at describing how tasks are assigned among the members of colonies of Mischocyttarus cassununga (Von Ihering) during the postemergence phase. For this, we daily tape recorded the behavioral repertoire of thirteen colonies in the field, later analyzing the results of each colonial subphase with Statistic analysis (Principal Component Analysis, Clustering Analysis and ANOVA - Tukey-Kramer t-test p<0.05). Our results showed that the assignment of tasks in M. cassununga generally reflects the dominance hierarchy. Despite of the behavioral flexibility of basal eusocial wasps (or absence of a well-defined temporal polyethism), it was possible to identify different groups of subordinate females (workers) in the colony. The division of labor during the pre-male subphase was delineated with four defined groups, whereas the post-male subphase with three groups. Pre-male: G1 - a dominant group of reproductive females, G2 - a group of higher hierarchically subordinate females (these can sometimes perform tasks very similar to the queens), G3 - a subordinate group of forager females, and G4 - a subordinate group of inactive and principally young wasps. Post-male: G1, G2 and G3 (similar to groups during pre-male subphase), but without G4. We think these analyses suggest a novel view of the importance of the behavioral repertoire of higher hierarchically subordinate females in wasp nests, at least in the genus Mischocyttarus.
Keywords: Behavioral repertoire; Dominance hierarchy; Mischocyttarini; Polistinae; Social biology